Simultaneous removal of multiple polycyclic aromatic hydrocarbons (PAHs) from urban stormwater using low-cost agricultural/industrial byproducts as sorbents. (July 2021) - Esfandiar, Narges; Suri, Rominder; McKenzie, Erica R.
Abstract: The potential of five low-cost and globally available sorbents, including three raw waste products – waste tire crumb rubber (WTCR), coconut coir fiber (CCF) and blast furnace slag (BFS) – and two modified materials – biochar (BC) and iron coated biochar (FeBC) – were evaluated for removing a mixture of polycyclic aromatic hydrocarbons (PAHs): pyrene (PYR), phenanthrene (PHE), acenaphthylene (ACY) and naphthalene (NAP) from simulated stormwater. The physicochemical characteristics of the sorbents were assessed by BET-N2 surface area, CHN elemental analysis, FTIR and scanning electron microscope (SEM-EDS). The experimental data were well described by both linear and Freundlich isotherm and pseudo-second order kinetic models. The adsorption rate was mainly controlled by the film diffusion mass transfer mechanism. The magnitude of PAHs partition coefficients ( K d ) followed the order of BC > FeBC > WTCR > CCF ≫ BFS, ranging from 80 to 390, 000 L/kg. The sorption K d values were positively correlated with both aromaticity of sorbents and octanol-water partition coefficients ( K ow ) of PAHs. Solution ionic strength and pH did not have significant effects on the sorption of PAHs by all sorbents. In contrast, humic acid, as dissolved organic carbon, decreased sorption capacities of WTCR and CCF, and increased sorption efficiency of BFS, which was confirmed with field-collected real stormwater. The hydrophobic π–π interactions were the main mechanism for the sorption of PAHs by various sorbents. These findings are promising for future development of cost-effective sorption filters for removal of hydrophobic organic pollutants from urban stormwater runoff. Graphical abstract: Image 1 Highlights: High PAHs sorption from stormwater was achieved by raw and modified materials. PAHs removal occurred rapidly and reached equilibrium <4 h. PAHs sorption increased with the increase in aromaticity of sorbents. Humic acid significantly affected the PAHs sorption onto raw sorbents. Solution pH and ionic strength had no significant effect on PAHs sorption process.